Structuring the Authority of the DPD RI as Consistency in the Bicameral System - Palenewen, Jovano Deivid Oleyver (Universitas Brawijaya, 2020)
One of the ways in which power is exercised in Indonesia lies with the legislative body whose principle of power is an institution that represents society. The constitutional structure of the legislative body, by various groups, says that it uses a bicameral system which has two chambers in carrying out the mandate of representation, namely the DPR and DPD. The implementation of the legislative powers by these two institutions is not balanced with the weakness of the authority possessed by the DPD. While the institutions are the same in the position of representation from each region. So there needs to be an effort in the formulation to increase the role of the DPD in carrying out its duties and responsibilities. This writing uses qualitative methods, with data taken from literature sources. The author tries to build the argument that the exercise of political power carried out by the DPD Ri institution needs to be reorganized in increasing its role to carry out its duties and functions as regional delegates in consistency with the bicameral system.Â Keywords: Parliament, DPD, bicameral.